Valuation method for sub-indicators of rock burst risk based on mining depth and tectonic stress - Zhen LI; Guanyang WU; Shangjin SI; Xin GAO; Xun LIU; Dongdong ZHANG; Chengxiang ZHANG; Jiachen LIU (Meitan kexue jishu)
The mechanical properties of deep rocks differ from those of the shallow layers due to the complex environment. Rock burst disasters are often induced under the disturbance of coal mining. The rock burst risk assessment plays an important role in the prevention of dynamic disasters. However, in the calculation of the sub-indicators for the comprehensive index method considering the influence of geostress factor W5, there is no clear basis for determining the normal stress value. To address this issue, the current situation of coal mining depth and the distribution law of geostress in China were firstly clarified. The range of the mining depth and geostress in the numerical research was then determined. Based on laboratory test results, a numerical model was established and simulations of underground excavation were carried out. The evolution law of the failure volume was analysed, revealing the evolutionary relationship between the stress ratio near high geostress manifestation points and mining depth. A quantitative expression for the critical crustal stress ratio and a criterion for high geostress manifestations were established. Finally, a new sub-indicator of rock burst risk index based on mining depth and geostress was proposed. The results are as follows. Firstly, the high geostress behavior and dynamic instability of coal-rocks are generally obvious in the rock burst. In this case, high geostress manifestations and strong failure characteristics can be identified as “deep” conditions. Secondly, the failure volume of the underground rock increases with the increasing crustal stress ratio and buried depth, with variations in the failure volume curves depending on the rock type. Thirdly, the critical crustal stress ratio, which corresponds to the limit of high geostress, decreases exponentially with the increase of buried depth. When the buried depth tends to the infinity, the critical geostress ratio tends to 0.6. Fourthly, when the crustal stress ratio is greater than or equal to the critical crustal stress ratio, the characteristics of high geostress manifestations occur. Lastly, the value of the normal stress can be defined as the maximum horizontal crustal stress corresponding to the occurrence point of high geostress manifestation. The proposed sub- indicators accurately evaluate rock burst risks under different mining depths and tectonic stress conditions, highlighting the personalized characteristics in the prevention of rock burst.